Factors Associated with the Utilization of Health Services in the Working Area of the Community Health Center - Istiqamah, Nurul Fajriah; Sirajuddin, Inayyah Nur Fitry (Journal of Scientific Insights, 2026)
Primary health care utilization at Bantimurung Community Health Center in Maros District is influenced by individual factors such as sex, marital status, health insurance ownership, and accessibility. This quantitative cross-sectional study involved 395 respondents from a population of 31,949 residents, selected via cluster random sampling and Slovin's formula. Univariate analysis revealed an 86.1% service utilization rate, with 89.4% insurance coverage and 80% accessibility. Bivariate Chi-square tests showed a significant association between health insurance ownership and utilization (p=0.001), while sex (p=0.189), marital status (p=0.160), and accessibility (p=0.069) were not significant. These findings highlight the dominant role of financial enabling factors in supporting Universal Health Coverage through Indonesia's JKN program.